Imbalance of synaptic actin dynamics as a key to fragile X syndrome?. (25th February 2018) - Michaelsen‐Preusse, Kristin; Feuge, Jonas; Korte, Martin
Abstract: Our experiences and memories define who we are, and evidence has accumulated that memory formation is dependent on functional and structural adaptations of synaptic structures in our brain. Especially dendritic spines, the postsynaptic compartments of synapses show a strong structure‐to‐function relationship and a high degree of structural plasticity. Although the molecular mechanisms are not completely understood, it is known that these modifications are highly dependent on the actin cytoskeleton, the major cytoskeletal component of the spine. Given the crucial involvement of actin in these mechanisms, dysregulations of spine actin dynamics (reflected by alterations in dendritic spine morphology) can be found in a variety of neurological disorders ranging from schizophrenia to several forms of autism spectrum disorders such as fragile X syndrome (FXS). FXS is caused by a single mutation leading to an inactivation of the X‐linked fragile X mental retardation 1 gene and loss of its gene product, the RNA‐binding protein fragile X mental retardation protein 1 (FMRP), which normally can be found both pre‐ and postsynaptically. FMRP is involved in mRNA transport as well as regulation of local translation at the synapse, and although hundreds of FMRP‐target mRNAs could be identified only a very few interactions between FMRP and actin‐regulating proteins have been reported and validated. In this review we give an overview of recent work by our lab and others providing evidence that dysregulated actin dynamics might indeed be at the very base of a deeper understanding of neurological disorders ranging from cognitive impairment to the autism spectrum. Abstract : The role of the fragile X mental retardation protein (FMRP) in the regulation of actin in dendritic spines by direct interaction. mRNAs of actin‐binding proteins can be targeted to dendrites as well as dendritic spines where they are locally translated upon need and crucially involved in processes of synaptic plasticity – a mechanism that might be dysregulated in fragile X syndrome.